2010
DOI: 10.1073/pnas.1010459107
|View full text |Cite
|
Sign up to set email alerts
|

Regional aerobic glycolysis in the human brain

Abstract: Aerobic glycolysis is defined as glucose utilization in excess of that used for oxidative phosphorylation despite sufficient oxygen to completely metabolize glucose to carbon dioxide and water. Aerobic glycolysis is present in the normal human brain at rest and increases locally during increased neuronal activity; yet its many biological functions have received scant attention because of a prevailing energy-centric focus on the role of glucose as substrate for oxidative phosphorylation. As an initial step in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
642
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 609 publications
(686 citation statements)
references
References 63 publications
42
642
0
2
Order By: Relevance
“…The functional imaging group at Washington University at St Louis specifically Marcus Raichle and his colleagues are in direct conflict with this work and our conclusions based on their recent paper (Vaishnavi SN et al (2010) Regional aerobic glycolysis in the human brain. Proc Natl Acad Sci USA 107:17757-17762).…”
Section: Disclosure/conflict Of Interestmentioning
confidence: 73%
See 2 more Smart Citations
“…The functional imaging group at Washington University at St Louis specifically Marcus Raichle and his colleagues are in direct conflict with this work and our conclusions based on their recent paper (Vaishnavi SN et al (2010) Regional aerobic glycolysis in the human brain. Proc Natl Acad Sci USA 107:17757-17762).…”
Section: Disclosure/conflict Of Interestmentioning
confidence: 73%
“…[31][32][33][34][35] The meta-analysis was composed of CMR O2 and CMR glc values from as few as 23 and as many as 46 distinct brain areas in 109 subjects. BioImage Suite (www.…”
Section: Regional Oxidative Demand For Glutamatergic Activity In the mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent whole-brain voxelwise analysis, 6 it was showed that regional cerebral blood flow (rCBF) measured with arterial spin labeling (ASL) significantly correlated with three nodal topological centrality measures (mean functional connectivity strength, local efficiency, and betweenness centrality) in an extensive resting-brain network estimated from blood-oxygen-level-dependent (BOLD) activity correlations. Given that rCBF is, in turn, closely related to basal cerebral metabolism, 7,8 the tight association between local centrality measures and rCBF suggests an underlying metabolic basis for highly connected and/or highly centralized functional hubs. Moreover, these findings were broadly consistent with an earlier voxelwise analysis of fMRI data that had found a highly significant association between amyloid-b deposition in Alzheimer's disease (AD), a metabolically driven process, 9 and the nodal degree centrality.…”
Section: Introductionmentioning
confidence: 99%
“…The above studies show that the resting brain also releases small amounts of lactate (B3% to 7% of glucose uptake), and that lactate efflux quickly increases by 3-to 4-fold during activation. A recent positron emission tomographic study in a resting young adult human brain revealed regional heterogeneity in the mismatch between local rates of glucose and oxygen utilization (Vaishnavi et al, 2010), suggesting that lactate release from various brain structures probably differs under basal conditions. …”
mentioning
confidence: 99%